EXPLORING THE EXPERIENCES OF SECONDARY SCHOOL ADMINISTRATORS AMONG STATE UNIVERSITIES AND COLLEGES IMPLEMENTING THE K TO 12 PROGRAM - Romeo Jr G. Pabiona (Universitas Negeri Islam Sumatera Utara, 2025)
This study explored the lived experiences of the Secondary School Administrators in the SUCs implementing the K to 12 Program in Region X, during the school year 2016-2017 up to 2019-2020. It utilized a qualitative research design using the phenomenological-descriptive approach. Narrative analysis of (Collaizi, 1978) used as basis of presentation and interpretation of the data. The participants of the study were the administrators of the four SUCs in Region X offering high schools and the eight senior faculty randomly selected by their respective administrators in both JHS and SHS. It utilized interviews, focus group discussion, and school records to gather data. The interview guide and FGD motive questions underwent validation from the panel of experts before the finalization and implementation. An audio-recorder served as the equipment to record the discourses from the interview and the FGD. After the transcriptions, clustering of the significant statements formed the themes and sub-themes. The findings showed four distinct themes that surfaced out. These themes are: (1) believe to achieve, (2) support and report the effort, (3) assessment for advancement, and (4) transparency and efficiency. The secondary school administrators are faced with the challenges on limited school facilities, problems in coping with school responsibilities, and problems on less exposure to the K to 12 Program. Coping and honing mechanisms were the management strategies used. They also encountered challenges in PTA empowerment, delegation of responsibilities, and proper time management. Management by empowerment was the strategy used.